Identification and Activity of The Retrotranposon Tos17 in Indonesian Javanica Rice CV.Rojolele And Japonica Rice CV. Gajahmungkur - Nugroho, Satya; Loedin, Inez HS; Ouwerkerk, Pieter BF (ANNALES BOGORIENSES, 2007)
Retrotransposons arc  mobile  genetic  elements  that  transpose  via  an  RNA intermediate  that  is  reverse transcribed  before  integration  into  a  new  location  within  the  host  genome. They  are  ubiquitous  in  eukaryotic organism.  and constitute a major portion of the nuclear genome (often more than half of the total DNA) in plants .Tos17 is a  rice  endogenous  retrotransposon  on  that  has  been  studied  thoroughly. Tos17 has  been  shown  to  be  an efficient insertional mutagen and saturation mutagenesis tool for gene tagging and functional genomics in Japonicarice cv  Nipponbare.  In  lavanica rice however, the presence and activity of  Tos17 has not been described thus far. while in some Indica rice Tos17 has  been found  to be  inactive. Javanica rice, also known as tropical  Japonica rice,has many cultivars which may serve as pontetial genetic resources of great interest for breeding programmes. Here  , the presence and activities of retrotransposon Tos17 in  Javanica rice  cv Rojolele was described and compared  to those of Japonica rice and Japonica rice cv Gajahmungkur We  identified  five and theree copies of  Tos17 in Rojolele and Gajahmungkur, respeclively, with different activities.Keywords: Oryza  sativa, rice, javanica, retrotransposon, Tos17